Clinical Practice Guidelines for Hypertensive Emergency Treatment - Carlos Garcia Gomez; Raúl Nieto Cabrera (Medisur)
Clinical Practice Guidelines for Hypertensive Emergency Treatment. It has been defined as the abrupt increase of systolic and diastolic blood pressure (usually ≥ 220/140 mmHg) associated with organic damage mainly of the central nervous system, heart or kidneys. This document includes concepts, different presentations, diagnosis and treatment, stressing the function of the most frequent hypotensive medications. It includes assessment guidelines focused on the most important aspects to be accomplished.